Intratumorale Heterogenität des Nierenzellkarzinoms: Molekulare Grundlagen und translationale Implikationen = TumorsuppressorgenIntratumoral heterogeneity in renal cell carcinoma : molecular basis and translational implications - Höfflin, Rouven; Roth, Wilfried; Sültmann, Holger; Grüllich, Carsten; Hatiboglu, Gencay; Nyarangi-Dix, Joanne; Schoenberg, Gita; Teber, Dogu; Hadaschik, Boris; Pahernik, Sascha; Hohenfellner, Markus; Duensing, Stefan (Der Urologe, 2015)
Advanced clear cell renal cell carcinoma is characterized by extensive intratumoral genomic heterogeneity and branched as well as convergent evolutionary traits with genomically different subclones evolving in parallel in the same tumor. Distinct driver mutations can be found in spatially separated subclones, which may hinder the development of novel targeted therapies. However, truncal mutations of the VHL tumor suppressor gene and chromosome 3p loss were ubiquitously detected and will hence continue to be a focus of future drug development. Nevertheless, genomic instability, enhanced tumor genome plasticity and intratumoral heterogeneity are likely to represent major challenges towards biomarker development and personalized patient care.